Optimizing the Energy Efficiency of Message Exchanging for Service Distribution in Interoperable Infrastructures - Bessis, N.; Sotiriadis, S.; Pop, F.; Cristea, V. (2012 4th International Conference on Intelligent Networking and Collaborative Systems, 2012)
Optimizing the competence of message exchanging algorithm in large-scale grids and inter-clouds could be proven to be a crucial factor in achieving an efficient resource management. Traditional solutions usually incorporate either probabilistic or flooding message exchanging techniques mainly due to the dynamic and unpredictable formation of the infrastructure. Our vision encompasses a total decentralized nodes topology in which message exchanging algorithm allows dissemination of communication messages within a decoupled node formation setting. We consider various e-infrastructure nodes that exchange simple messages with linking nodes regarding resource competence for executing certain service(s) requirements. The optimization criterion is to improve the energy efficiency of the network performance for message exchanging in two cases as follows. Firstly, a requester sends messages to all interconnected nodes and gets messages only from resources available to execute it. Secondly, the requester sends one message for all of the jobs of its local pool and gets a respond from available nodes, and then obtainable resources are ranked and hierarchically categorized based on the performance criterion e.g. latency competency. The algorithm is simulated and results obtained are very supportive.